2017
DOI: 10.1128/mbio.00824-17
|View full text |Cite
|
Sign up to set email alerts
|

First Insights into the Diverse Human Archaeome: Specific Detection of Archaea in the Gastrointestinal Tract, Lung, and Nose and on Skin

Abstract: Human-associated archaea remain understudied in the field of microbiome research, although in particular methanogenic archaea were found to be regular commensals of the human gut, where they represent keystone species in metabolic processes. Knowledge on the abundance and diversity of human-associated archaea is extremely limited, and little is known about their function(s), their overall role in human health, or their association with parts of the human body other than the gastrointestinal tract and oral cavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
183
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 191 publications
(192 citation statements)
references
References 73 publications
(111 reference statements)
7
183
1
1
Order By: Relevance
“…Although understudied, archaea are consistently identified in human microbiota studies and their community composition differs according to body site (Koskinen et al, 2017). Methonoarchaea, including Methanobrevibacter smithii and Methanosphaera stadtmanae (M. stadtmanae), have been proposed as keystone members of this microbial community and possess immunogenic properties (Blais Lecours et al, 2011;Bang et al, 2014).…”
Section: Archaea-emerging Players In Human Gutmentioning
confidence: 99%
“…Although understudied, archaea are consistently identified in human microbiota studies and their community composition differs according to body site (Koskinen et al, 2017). Methonoarchaea, including Methanobrevibacter smithii and Methanosphaera stadtmanae (M. stadtmanae), have been proposed as keystone members of this microbial community and possess immunogenic properties (Blais Lecours et al, 2011;Bang et al, 2014).…”
Section: Archaea-emerging Players In Human Gutmentioning
confidence: 99%
“…Furthermore, Koskinen et al (2017) have shown for the first time that archaea reveal a body site specific pattern, similar to bacteria: the gastrointestinal tract being dominated by methanogens, the skin by Thaumarchaeota, the lungs by Woesearchaeota, and the nose archaeal communities being composed of mainly methanogens and Thaumarchaeota. Altogether, this indicates a substantial presence of archaea in some, or even all, human tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, (methanogenic) archaea are part of the commensal microorganisms inhabiting the human body, being regularly detected in the oral cavity and the gastrointestinal tract (Chaudhary et al, 2015;Gaci et al, 2014;Horz and Conrads, 2011;Nkamga et al, 2017); in the latter they sometimes even outnumber the most abundant bacterial species (14%, (Tyakht et al, 2013);). Most human archaea studies use either cultivation or qPCR methods (Grine et al, 2017;Koskinen et al, 2017;van de Pol et al, 2017;Wampach et al, 2017) and only a few, 16S rRNA gene-based archaeacentric studies are available Moissl-Eichinger et al, 2017). These new studies have shown that archaea are also present in the human respiratory tract and on human skin in considerable amounts Probst et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…When the human intestinal microbiome was first catalogued through the metagenomic analysis of stool samples, previously unknown bacterial taxa were discovered , . In addition to bacteria, the human gut microbiome includes archaea (which constitute ∼10% of the anaerobic intestinal flora), eukaryotic microorganisms, and viruses that infect bacteria or archaea (phages) . The presence of phages indicates that viruses can contribute to microbiome population dynamics by infecting and killing sensitive prokaryotes or transducing DNA segments between cells.…”
Section: Syntrophic Symbiotic Associations Microbiomes and Holobiontsmentioning
confidence: 99%